ASSESSING THE TRANSFORMATION OF LIVELIHOODS IN ILLEGAL GOLD MINING COMMUNITIES - Ardikoesoema, Nurmansyah; Karuniasa, Mahawan (Journal of Environmental Science and Sustainable Development, 2025)
Illegal Artisanal Small-Scale Gold Mining (PETI) in Poboya, Palu City, exemplifies Indonesia’s nexus of socio-environmental vulnerability and institutional marginalization. Although environmental degradation, health impacts, and regulatory challenges associated with PETI have been extensively documented, limited research has systematically examined how the interplay of capital assets and internal motivation drives livelihood transformation pathways within PETI communities. To address this gap, this study uniquely integrates the Sustainable Livelihood Framework with spatial analysis to assess the combined influence of environmental, social, and economic capitals on PETI livelihood transitions. Using a mixed-methods approach, data were collected through quantitative survey and qualitative in-depth interviews with 119 PETI workers selected through purposive and convenience sampling analyzed using Atlas.ti and spatial data analyzed using Geographic Information Systems (GIS). Quantitative analysis using multiple linear regression revealed that environmental capital (β=0.288), social capital (β=0.400), economic capital (β=0.304), and motivation to change (β=0.340) had significant positive effects (p<0.001) on livelihood transformation. Qualitative narrative analysis revealed that persistent informal institutional networks, constrained access to formal financing, and perceptions of repressive policy frameworks continue to sustain PETI activities despite environmental and legal risks. Spatial analysis demonstrated that PETI activities are concentrated in high mineral potential zones with informal accessibility, underlining the combined role of ecological opportunity and socio-economic necessity. This study contributes to the literature by providing empirical evidence on how capital assets and motivation interact spatially and socially to influence livelihood transformation, offering a more integrated perspective beyond prior research that predominantly focused on environmental impacts and regulatory issues. The findings underscore the need for policy interventions that combine capital strengthening, motivational mobilization, and inclusive institutional reforms to facilitate fair, legal, and sustainable livelihood transitions for PETI communities.